SEM OBSERVATIONS OF VOLCANIC ASH AT 500M DEPTH IN THE MIZUHO ICE CORE - ヒガシ, アキラ; フジイ, ヨシユキ; タケヤ, サトシ; HIGASHI, Akira; FUJII, Yoshiyuki; TAKEYA, Satoshi (National Institute of Polar Research, 1994)
P(論文) A visible volcanic ash layer was found at approximately 500.7m depth in the Mizuho core (Y. FUJII and O. WATANABE; Ann. Glaciol., 10,38,1988). A 50cm core sample which contained the ash layer was not included in the preliminary quantitative anlyses of δ^<18>O, microparticles by Coulter counter, electrical conductivity, pH and major ions, of which 50cm length samples were taken at 2m intervals all through the core (O. WATANABE et al.; JARE Data Rep., 181 (Glaciology 20), 79p., 1992). Most of the ash layer has been kept for detailed analyses using more sophisticated techniques in the near future. Recently, preliminary analyses of the ash by a scanning electron microscope (SEM) and also by energy dispersive spectra (EDS) have been done as presented here. Several grams of ice were taken from a depth of 500.665-500.700m where the ash concentration was visibly thick. The sample was cut and melted in the same way as we adopted in our SEM observations of microparticles contained in medium depth ice cores retrieved in Queen Maud Land, Antarctica (A. HIGASHI et al.; Bull. Glacier Res., 8,1,1990). Volcanic ash particles were collected on a Nucleo filter by filtering the melt water through it, and its small portion was adhered on a specimen holder of a SEM and coated with evaporated carbon in vacuum. The SEM is a JSM-T220,JEOL, attached to a QX-2000,Link for the EDS analysis. For the quantitative elemental analysis using EDS, a cobalt standard and ZAF4 program were used. Several particles which look like vesicular tephra or volcanic glass shard in SEM photographs were analyzed quantitatively by EDS. Computed data of oxides plotted on a diagram of Na_2O+K_2O vs. SiO_2 show that the present volcanic ash belongs to the non-alkaline area in the diagram. Compared with data of other ashes found in bare ice areas in the Yamato Mountains (T. KATSUSHIMA et al.; Mem. NIPR, Spec. Issue, 34,174,1984) and at 100.8m depth of the Vostok core and 303.44m depth of the South Pole core (J.M. PALAIS et al.; Geophys. Res. Lett., ...